Effect of Black Tea and Black Tea Pomace Polyphenols on α-Glucosidase and α-Amylase Inhibition, Relevant to Type 2 Diabetes Prevention - Striegel, Lisa; Kang, Bouhee; Pilkenton, Sarah J.; Rychlik, Michael; Apostolidis, Emmanouil (Frontiers in Nutrition, 2015)
This study evaluates the potential mechanism of action and bioactivity of black tea and black tea pomace for type 2 diabetes prevention via inhibition of carbohydrate hydrolyzing enzymes. Black tea leaves were extracted in hot water and black tea pomace was extracted in 70% acetone. The phenolic content of the water extract (WBT) and pomace acetone extracts (AOBT) were 5.77 mg/mL, and 8.9 mg/mL, respectively, both based on the same concentration of solid tea in the extract. The water extract was subjected to C18 extraction and the recovered hydrophobic fraction (HBBT) was further subjected to LH-20 extraction to recover a low molecular weight phenolic enriched fraction (LMW) and a high molecular weight enriched fraction (HMW). The phenolic content of the LMW and HMW fraction were 1.42 mg/mL and 2.66 mg/mL, respectively. Among water extracts the HMW fraction was most bioactive against α-glucosidase (IC50=8.97 µg/mL) followed by HBBT fraction (IC50=14.83 µg/mL). However the HBBT fraction was the most bioactive fraction against α-amylase (IC50=0.049 mg/mL). The black tea pomace (AOBT) had significant α-glucosidase inhibitory activity (IC50=14.72 µg/mL) but lower α-amylase inhibitory activity (IC50=0.21 mg/mL). The phenolic profiles for LMW and HMW fractions were evaluated using HPLC and the differences between the two profiles were identified. Further research is underway to identify and evaluate the phenolic compounds that are present in the HMW fraction. Our findings suggest that black tea and black tea pomace has potential for carbohydrate hydrolyzing enzyme inhibition and this activity depends on high molecular weight phenolic compounds.